Multinational enterprises and sustainable development - Ghauri, Pervez N., 1948-; Fu, Xiaolan, 1967-; Väätänen, Juha (International business and management series ;, 2017)
Multinational enterprises (MNEs) are believed to contribute towards economic development of host countries through foreign direct investment (FDI), which results in poverty alleviation and human empowerment through linkages and spillovers with local stakeholders. However, earlier research demonstrates that the positive impact of FDI is often inconclusive. There is thus a gap in understanding the link between the activities of MNEs in developing countries and their impact on socio-economic development. This volume reports the results of a large international 'MNEmerge' research project, financed by the European Commission, and provides an understanding of the impact of MNEs on United Nations Millennium Development Goals and successive Sustainable Development Goals in developing countries.